Features’ Enterprises Related to Environmental Protection and Environmentally Friendly Products for Sustainable Industries of Kazakhstan - DAMBAULOVA, Gulmira; KOVAL, Andrey; MUKATAY, Aigul; KAIDAROVA, Saida; DAULETOVA, Aziza; KURMANOVA, Gulnara (Journal of Environmental Management and Tourism, 2022)
Creating favorable conditions for the sustainable industries is an important task of the present generation associated with the action of a complex of economic, industrial, environmental and social factors that ensure their transformation in accordance with the changing environmental factors. This study shows the dynamics of changes in sustainable industries, highlights the features of Kazakhstani enterprises, calculates their share of activities in the volume of industry, the contribution of regions to the republican volume of industry, the financial stability of industrial enterprises, the disposal of fixed assets, the level of investment in fixed capital of industry in conjunction with production environmentally friendly products.